2019
DOI: 10.1002/cbdv.201900427
|View full text |Cite
|
Sign up to set email alerts
|

The Development Process: from SAHA to Hydroxamate HDAC Inhibitors with Branched CAP Region and Linear Linker

Abstract: Histone deacetylases (HDACs) belong to a group of epigenetic regulatory enzymes that participate in modulating the acetylation level of histone lysine residues as well as non-histone proteins, and they play a key role in the regulation of gene expression. HDACs are potential anticancer drug targets highly expressed in various kinds of cancer cells. So far, five small molecules targeting HDACs have been approved for the therapy of cancer, and over 20 inhibitors of HDACs are under different phases of clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In general, HDACs are epigenetic regulatory enzymes regulating the acetylation of histone lysine residues and nonhistone proteins and are important mediators of gene expression (F. Yang, Zhao, Hu, Jiang, & Zhang, 2019). In a fungal model, HDACs are shown to collaboratively repress or activate secondary metabolite production (Lan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, HDACs are epigenetic regulatory enzymes regulating the acetylation of histone lysine residues and nonhistone proteins and are important mediators of gene expression (F. Yang, Zhao, Hu, Jiang, & Zhang, 2019). In a fungal model, HDACs are shown to collaboratively repress or activate secondary metabolite production (Lan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by replacing the hydrogen atom (H) at the C2 position of SAHA's hydrophobic long chain with aliphatic or aromatic hydrocarbons, a new analog named C2-R-SAHA was created. This analog has shown the ability to enhance its selectivity for HDAC6 and 8 [147]. Thanks to the molecular docking approach, highly conserved active catalytic regions across all HDAC isoforms were observed, with class I HDAC exhibiting a narrower hydrophobic channel than HDAC6.…”
Section: Isohydroxamic Acidsmentioning
confidence: 99%
“…Studies have shown that modifying the hydrophobic long chain of SAHA can enhance its selectivity for HDAC. For instance, substituting the hydrogen atom (H) at the C2 position of the hydrophobic long chain of SAHA with aliphatic or aromatic hydrocarbons resulted in the analog C2-R-SAHA, which effectively improved its selectivity for HDAC6 and 8 (Yang et al, 2020).…”
Section: Sahamentioning
confidence: 99%